2021
DOI: 10.1002/eahr.500085
|View full text |Cite
|
Sign up to set email alerts
|

Governing AI‐Driven Health Research: Are IRBs Up to the Task?

Abstract: Many are calling for concrete mechanisms of oversight for health research involving artificial intelligence (AI). In response, institutional review boards (IRBs) are being turned to as a familiar model of governance. Here, we examine the IRB model as a form of ethics oversight for health research that uses AI. We consider the model's origins, analyze the challenges IRBs are facing in the contexts of both industry and academia, and offer concrete recommendations for how these committees might be adapted in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…First, they challenge traditional research principles such as data privacy, informed consent, scientific validity of research, risk assessment, and distribution of benefits ( Price & Cohen, 2019 ; Rivas Velarde et al, 2020 ). Second, they introduce new epistemic challenges related to the assessment of scientific validity, technological reliability, accountability, fairness, and transparency ( Friesen et al, 2021 ). Finally, they challenge the very notion of human participants in research, as they enable retrospective data processing without physical interaction with research participants ( Metcalf & Crawford, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, they challenge traditional research principles such as data privacy, informed consent, scientific validity of research, risk assessment, and distribution of benefits ( Price & Cohen, 2019 ; Rivas Velarde et al, 2020 ). Second, they introduce new epistemic challenges related to the assessment of scientific validity, technological reliability, accountability, fairness, and transparency ( Friesen et al, 2021 ). Finally, they challenge the very notion of human participants in research, as they enable retrospective data processing without physical interaction with research participants ( Metcalf & Crawford, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ethics review boards must demand this type of transparency and fairness in the creation of models so that systems that harness machine learning can be implemented in real clinical practice with low risk. Some discussion of this path forward has been brought to light by Friesen et al (2021) who reported on IRBs as a means of ethics oversight in health research that harnesses AI.…”
Section: Discussionmentioning
confidence: 99%
“…Facebook, for example, is carrying out a suicide prediction and prevention project, which relies exclusively on the information that users post on the social network [18]. Because this type of research is now possible, and the available ethics review model exempts many big data projects from ERC appraisal, gaps in oversight are growing [17,73]. Just as corporations can re-use publicly available datasets (such as social media data) to determine life insurance premiums [74], citizen science projects can be conducted without seeking research oversight [75].…”
Section: Novel Weaknesses: Purview Weaknessesmentioning
confidence: 99%